Foreign ownership, financial leverage dan price to earning ratio (P/E) - Pristin Prima Sari; Sri Hermuningsih (Sosio e-Kons, 2018)
This study aims to find empirical evidence of the influence of Financial Leverage, Foreign Ownership to Price ToEarning Ratio (P / E) on non-financial companies in Indonesia Stock Exchange (IDX) in 2012-2016. The samples in this research are 46 non-financial companies in Indonesia Stock Exchange in 2012-2016. Data in the form of panel with fixed effect method with inflation control variable and firm size. We use E-Views 9th Edition for analysis data. The results of this study simultaneously show that financial leverage with Debt to Equity (DER) as a proxy, foreign ownership, Inflation and firm size proportion have significant positive effect (0,000 significance) on price to earning ratio (P / E). Partially shows that Financial leverage has negativesignificant effect (significance 0.000) to P / E. Foreign ownership has negativesignificant effect (significance 0,000) to P / E. Inflation has no effect (significance 0.000) to P / E. Firm Size has negative significant effect (significance 0.000) to P / E. This research is useful for shareholders, corporate and government management in taking policies related to foreign ownership, financial leverage and price to earnings ratio (P / E).Keywords : Financial Leverage, Foreign Ownership, Price to Earning Ratio, IDX